Pesticidas organoclorados e organofosforados no sedimento do Rio Pelotas: risco ecológico, distribuição espacial e temporal - Model, Kathleen Jeniffer (2017)
The highest standard of human activity is associated to agricultural and industrial activities. Thus, aquatic sediments are the most used environmental files to evaluate anthropogenic contamination from atmosphere, soil and water, due to its adsorption capacity. Inadequate and uncontrolled use of pesticides has happened in order to increase agricultural yield, although it brings forth pollution problems and serious consequences for public health. Therefore, further surveillance has been required concerning pesticides’ use and sale as well as the environment monitoring. Thus, this study aimed at evaluating Pelotas River regarding its sediment quality and taking into account compounds such as orangiochloride and organophosphorous to determine the ecological risk, spatial and temporal distributions. For this purpose, sediment samples were collected in 8 points (6 into Pelotas River and 2 into Tributaries), whose collections were carried out quarterly. This trial covered the four hydrological seasons of the year, totaling four collections that were registered with Peterson dredger. The methodology used to determine the studied pesticides was QuEChERS. The p'p'-DDT is worth mentioning from the organochlorines, since it was found in all samples. This represents that it was observed in 53.23% of the contaminated samples, with 0.158 ppb as maximum value. While Isodrin has shown the highest organochlorine concentration - 0.502 ppb. The points PEL 05 and TRI 02 showed the highest representativeness of contamination by organochlorines, caused by the slope degree of the area and by agricultural portion of each part. Methyl parathion recorded the highest representativity, with 48.4% of the total contaminated samples for organophosphates, with 2.42 ppb as maximum concentrations, while Disulfoton showed the highest concentration of this class - 2.62 ppb. The organochlorines have not shown any ecological risk. But, for organophosphates, the maximum concentration of Disulfoton pesticide has indicated a risk coefficient with significant potential for adverse effects on organisms. In the spatial and temporal distributions for organochlorines, there was some predominance of those compounds at PEL 05, PEL 04 and TRI 02 points, whereas for orgnaphosphates, points such as PEL 00, PEL 02, PEL 04 and PEL 05 were predominant. In temporal distribution, for organochlorines, eight from the ten compounds were distributed in summer, seven of them during autumn and springtime. In organophosphates, the four quantified pesticides were recorded only during autumn month. However, in springtime, three of them were representative, but in summer and winter, only two of these compounds were observed. Consequently, since Pelotas River is a Class I river, it is evident that concentrations of both classes of the studied pesticides cannot be neglected. Organophosphates are much toxic, much volatile, more used as well as the most representative ones in concentrations and they also present an ecological risk. Besides, there is an evident need to monitor these compounds in soil, sediment, water and biota, so that there is sustainability concering its use and application, aiming at improving the environmental quality and preservation of this natural resource, in this case named as Pelotas River.